Limited Transmission of the Ectoparasitic Fungus Hesperomyces virescens between Lady Beetles - Ted E. Cottrell; Eric W. Riddick (Psyche: A Journal of Entomology)
The ectoparasitic fungus Hesperomyces virescens Thaxter (Ascomycota: Laboulbeniales) commonly infects the invasive lady beetle Harmonia axyridis (Pallas) and several other aphidophagous lady beetles in North America and Europe. We tested the hypothesis that bodily contact between adults of different lady beetle species supports horizontal transmission of H. virescens. We used laboratory assays to determine whether H. axyridis or Olla v-nigrum (Mulsant) harboring H. virescens (i.e., source beetles) transmit the fungus to noninfected target beetles H. axyridis, O. v-nigrum, Coccinella septempunctata L., Coleomegilla maculata (De Geer), or Hippodamia convergens Guerin-Meneville. Results indicate that intraspecific transmission (i.e., for the source beetles H. axyridis and O. v-nigrum) was common but interspecific transmission (i.e., from source H. axyridis or O. v-nigrum to target species) was low. Interspecific transmission occurred at low rates from H. axyridis to both C. septempunctata and O. v-nigrum and from O. v-nigrum to both C. septempunctata and H. convergens. Based upon our laboratory assays of forced pairings/groupings of source and target beetles, we predict that horizontal transmission of H. virescens between species of aphidophagous coccinellids is possible but likely rare.